Radioactive Coil Embolization of Intracranial Aneurysms: Minimal Inventory to Reach Target Activities in a Virtual Series of 154 patients - Mounayer, Charbel (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Recanalization after selective endovascular treatment of intracranial aneurysms with platinum coils has been widely reported in the literature. Beta radiation emitted from (32)P ion–implanted coils can prevent recanalization in animal models. A complete inventory of radioactive coils may not be realistic; our hypothesis was that it might not be necessary to reach target activities in most aneurysms. A limited supply of three or four types of coils may decrease the inventory difficulties related to the use of an isotope with a half-life of 2 weeks. METHODS: We reviewed 154 aneurysms selectively treated with standard coils. We calculated the volumetric activity obtained if all coils (simulation 1) were radioactive with linear activities of 0.13 (scenario I) or 0.26 μCi/cm (scenario II). Then, we simulated a treatment with standard coils plus a selection of radioactive coils limited to three (simulation 2) or four types of commonly used coils (simulation 3). Resulting activities were calculated and reported to the lesion volume. For each scenario and simulation, the percentage of lesions, in which the target volumetric activity (0.018 μCi/mm (3)) was reached, was reported. RESULTS: Success in reaching target volumetric activities varied from 55–99% according to different simulations. A supply of four types of coils was sufficient to reach target activities in 86–95% of patients commonly treated in our institution. Target activities were difficult to reach in giant aneurysms. CONCLUSION: It is feasible to reach target activities in most lesions by using a limited coil supply.